Adaption and validation of the German version of the basic psychological needs in physical education scale - Heckmann, Philip (2013)
It is important to understand students’ motivation regarding physical activity to investigate the global issue physical inactivity. Based on the self-determination theory (SDT: Ryan & Deci, 2002), which is one of the most important frameworks in explaining motivation, students need to be emotionally satisfied in order to put effort towards a certain goal. The Basic Psychological Needs Theory is one sub-theory of the self-determination theory, which explains that constructs of autonomy, competence, and relatedness need to be satisfied in all humans in order to increase well-being. It is important to understand students’ motivation regarding physical activity to investigate the global issue of physical inactivity. In order to adapt a scale to another language, a reliable and valid scale is necessary. This procedure allows further research on motivational issues in other countries as well as comparison studies. Therefore, the main aim of this study was to adapt the Greek Basic Psychological Needs in Physical Education Scale (BPN-PE: Vlachopulos, Katartzi, & Kontou, 2011) to German. After translating the scale, the BPN-PE scale’s factorability, internal consistency and testretest reliability were examined. Finally, factorial and construct validity of the BPN-PE scale were explained. The three-factor structure of autonomy, competence, and relatedness of the original scale was hypothesized to be the same in the adapted German version. After obtaining permission to conduct the research from local school principals, a pilot test with 5th grade students (n = 20), age 11-12, was conducted at one high school in Germany. Secondary educational institutions (Germany) were used to collect data from 7th to 10th grade students (n = 372). Finally, a third wave of data for the needs of the test-retest procedure was collected from 90 students. In order to examine the construct validity of the BPN-PE, two other scales (Perceived Autonomy Support Scale and Subjective Vitality Scale) were used as criterion validity instruments. All the BPN-PE factor scores showed moderate correlation with the Perceived Autonomy Support Scale and the Subjective Vitality Scale ranging between .33 and .61 which indicates satisfactory criterion validity. Cronbach’s alphas ranged from .705 to .875. The Principal Component Analysis revealed that three specific sets of items (autonomy, competence and relatedness) explained 68 % of the variance in the BPN-PE scale. Consequently, the translated BPN-PE scale is considered reliable and valid for German PE student population. Limitations of the study and further suggestions are discussed.